2011
DOI: 10.1186/1556-276x-6-555
|View full text |Cite
|
Sign up to set email alerts
|

The application of carbon nanotubes in target drug delivery systems for cancer therapies

Abstract: Among all cancer treatment options, chemotherapy continues to play a major role in killing free cancer cells and removing undetectable tumor micro-focuses. Although chemotherapies are successful in some cases, systemic toxicity may develop at the same time due to lack of selectivity of the drugs for cancer tissues and cells, which often leads to the failure of chemotherapies. Obviously, the therapeutic effects will be revolutionarily improved if human can deliver the anticancer drugs with high selectivity to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
207
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(226 citation statements)
references
References 100 publications
2
207
0
3
Order By: Relevance
“…To assess the stability of CNT/miRNA complexes, heparin 5,000 U/mL (Teva Pharmaceutical Industries, Petah Tikva, Israel) was added to CNT/ miRNA complexes, and the displacement of the complex was monitored after incubating for 30 and 60 min. To test the supernatant toxicity also, cells were treated with supPEI-CNTs and supPAM-CNTs at the same concentration of polymers (4,8,12 and 20 μg/mL) or CNTs (10,20,30 and 50 μg/mL).…”
Section: Gel Retardation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the stability of CNT/miRNA complexes, heparin 5,000 U/mL (Teva Pharmaceutical Industries, Petah Tikva, Israel) was added to CNT/ miRNA complexes, and the displacement of the complex was monitored after incubating for 30 and 60 min. To test the supernatant toxicity also, cells were treated with supPEI-CNTs and supPAM-CNTs at the same concentration of polymers (4,8,12 and 20 μg/mL) or CNTs (10,20,30 and 50 μg/mL).…”
Section: Gel Retardation Assaysmentioning
confidence: 99%
“…[1][2][3][4] Recent findings in nanomedicine have revealed that CNTs can be used as potential drug carriers, therapeutic agents and diagnostics tools as well. [5][6][7][8][9][10] In particular, due to their ability to cross cellular membranes, their nanosize dimension, high surface area and relatively good biocompatibility, CNTs have also been employed as a novel gene delivery vector system. [11][12][13] However, one of the major drawbacks is their low solubility and high propensity to aggregate in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…4 The unique ability of CNTs to penetrate cell membranes enables them to deliver therapeutic agents into the cytoplasm and in many cases the nucleus of the cell. 5,6 Different strategies have been developed that load drug molecules onto CNTs through either covalent bonds or noncovalent adsorption. [7][8][9][10] However, covalent bonds between the CNT and carrier are inadequate, because a slight change in the…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes are used in drug delivery carriers for treatment of cancer [20]. And they are reported for targeting of amphotericin B to cells [21].…”
Section: Applications Of Carbon Nanotubes 1)mentioning
confidence: 99%